The potential of indigenous bacteria from oil sludge for biosurfactant production using hydrolysate of agricultural waste - NI’MATUZAHROH NI’MATUZAHROH; SILVIA KURNIA SARI; IRINE PUSPA NINGRUM; APRILLA DILA PUSFITA; LISA MARJAYANDARI; NASTITI TRIKURNIADEWI; SYAHRIAR NUR MAULANA MALIK IBRAHIM; FATIMAH FATIMAH; TRI NURHARIYATI; TINI SURTININGSIH; HANIF YULIANI (Society for Indonesian Biodiversity, 2019)
Abstract. Ni’matuzahroh, Sari SK, Ningrum IP, Pusfita AD, Marjayandari L, Trikurniadewi N, Ibrahim SNMM, Fatimah, Nurhariyati T, Surtiningsih T, Yuliani H. 2019. The potential of indigenous bacteria from oil sludge for biosurfactant production using hydrolysate of agricultural waste. Biodiversitas 20: 1374-1379. Biosurfactants are amphipathic compounds which are useful in various fields of health, industry, and remediation. Biosurfactants are produced by bacteria that grow in hydrocarbon or sugar substrates. Hydrolysis product of agricultural waste can be used as a biosurfactant production medium. This research aims to obtain biosurfactant producing bacteria from Balongan oil sludge, Indonesia. The ability to grow and produce biosurfactant by indigenous bacteria was tested using a medium of Synthetic Mineral Water (SMW) added by 209.3 ppm of rice straw hydrolysis product (RSHP). The growth of bacteria was evaluated through Total Plate Count (TPC) and biosurfactant production was evaluated through measurement of emulsification activity and surface tension. Six indigenous bacteria were capable to produce biosurfactants in the RSHP. Emulsification activity was not detected, but surface tension reduction was founded. The best biosurfactant was indicated by surface tension value of 53.56 mN/m with TPC value of 20.07 CFU/mL at the 5th day of incubation by BP (1) 5. The indigenous bacteria were identified as Propionibacterium BP (1) 1, Propionibacterium BP (1) 3, Bacillus BP (1) 4, Corynebacterium BP (1) 5, Corynebacterium BP (1) 8, and Rothia BP (1) 6. Utilization of sugar as hydrolysis product of agricultural waste is an innovation of raw materials for biosurfactant production.